Regularly-patterned nanorod light-emitting diode arrays grown with metalorganic vapor-phase epitaxy. (July 2015) - Tu, Charng-Gan; Su, Chia-Ying; Liao, Che-Hao; Hsieh, Chieh; Yao, Yu-Feng; Chen, Hao-Tsung; Lin, Chun-Han; Chen, Horng-Shyang; Kiang, Yean-Woei; Yang, C.C.
Highlights: Regularly-patterned GaN nanorod (NR) light-emitting diode (LED) arrays are grown. A top pyramid structure leads to purely non-polar sidewall quantum-well emission. The performance of an NR LED array is comparable to that of a planar LED. Abstract: The growth and fabrication of GaN nanorod (NR) light-emitting diode (LED) arrays have attracted much attention because of their advantages of higher crystal quality, larger sidewall emission area, and non-polar or semi-polar quantum well (QW) formation. In this paper, we review the development of regularly-patterned GaN NR LED arrays grown with metalorganic vapor-phase epitaxy. Such an array device is expected to be useful for practical lighting application. A regularly-patterned NR array is grown on a patterned template with either continuous or pulsed growth mode. Usually, with the pulsed growth mode, by switching group-III and V sources on and off alternatively, the NR geometry can be more uniform over an array. InGaN/GaN QWs can be deposited on the c -plane top face, m -plane sidewalls, and 1 1 ¯ 0 1 -plane slant facets on a c -axis-oriented NR with the highest (lowest) growth rate in the c -plane ( 1 1 ¯ 0 1 -plane). After the overgrowth of p-GaN on an NR with n-GaN core and QW deposition, an NR LED array can be implemented by covering the NRs with a transparent conductor. It has been demonstrated that the optical and electrical performances of an NR LED array can be comparable to those of a planar LED. Further developments in NR LED growth and process techniques can lead to an outperforming LED device with the NR structure.